PENGARUH SEKTOR PENDIDIKAN TERHADAP PERTUMBUHAN EKONOMI JAWA BARAT SELAMA PANDEMI - Sandi Mulyadi; Sri Mulyati (WELFARE: Journal of Islamic Economics and Finance, 2023)
West Java's economic growth shows a picture of local community economic activity that will generate added value for people's income in a certain period. One of the indicators in increasing economic growth is education. The purpose of this study was to examine the effect of education as proxied by Average Years of Schooling (RLS), Expected Years of Schooling (HLS), School Participation Rates (APS), and Government Expenditures on Education Sector (PPSP) on economic growth in West Java Province in 2017-2021. This study uses panel data regression analysis with the selected model, namely the fixed effect. The results of the test show that simultaneously the average length of schooling, expected length of schooling, school participation rates and government spending in the education sector affect economic growth in West Java Province during the pandemic. Partially, the average length of schooling, the expected length of schooling, and government spending in the education sector have a positive effect on economic growth. Meanwhile, the school enrollment rate has no effect on economic growth during the pandemic.